(untitled) (Altre Modernità, 2018)
A 2017 report by UCL Urban Laboratory has testified to an intensity of closures of LGBTQIA spaces in London over the last decade, particularly those catering to queer women, the trans community and/or queer people of colour. As Skelton and Valentine have shown, LGBT spaces play an important role in identity and community formation; loss of social space therefore has a direct impact on constructions of subjecthood, and the subject’s relationship to the urban. Focusing on London-based queer film festivals, this article will argue that, through the provision of material and discursive space, the queer film events constitute a strategic political tool of urban reclamation that resists material gentrification and neoliberal ideology. Furthermore, it will examine how the necessary engagement with issues of funding and corporate sponsorship intersect with festivals’ obligations to provide queer space for the community.